Impacto del Covid-19 en las actividades económicas - financieras de las cooperativas de ahorro y crédito del segmento tres - Macías Loor, María Gabriela (2023)
The purpose of this research is to determine the influence of covid-19 on the economic-financial activities of the savings and credit cooperatives of segment three, through the application of convenience sampling, it was possible to reach 38 organizations that were part of this investigation, same to which several calculations and their respective analyzes were applied. The financial bulletins of these entities were collected from the page of the Superintendency of Popular and Solidarity Economy, from 2017 to 2021. Different types of research were used, among which are: cross-sectional, causal, exploratory and quantitative for development from work; on the other hand, the applied methods were analytical and descriptive, essential for the execution of the phases; while the techniques used were the bibliographical review and the financial analysis for the knowledge of the antecedents and discussion of the results. For the analysis of the financial indicators, the PERLAS monitoring system was used, a tool capable of evaluating the variations of the accounting accounts. The results of the research project were divided into three phases: the first phase corresponded to the horizontal and vertical analysis of the balance sheet and the income statement with their respective discussion, the second phase is structured by the indicators established in the PERLAS system for the evaluation of the five years of study, the third and last phase consisted of the projections of the financial indicators for the knowledge of their future behavior based on the last years.